Larvicultura do pintado Pseudoplatystoma coruscans (Agassiz, 1829): aspectos da alimentação inicial e do desenvolvimento de estruturas sensoriais - Cestarolli, Marcos Antonio [UNESP] (2005)
The morphological development of the eye, chemo-, mechano- and electroreceptors was studied in Pseudoplatystoma coruscans (Siluriformes, Pimelodidade) embryos and larvae, kept in light and dark environments. The sensory structures development was appraised using light and electronic microscopy. Also, in both light conditions, the live food consumption (Artemia nauplii) was determined for different larval ages and at different prey densities. During the short embryonic stage (12 to 13 hours), the first cilia appeared in the olfactive region, which was covered by mechano- and sensory cilia, at hatching. In the first hours post-hatching, the olfactory pits were well defined and the number of cilia increased consistently. During this period, the primordial maxillary barbels developed, where taste buds quickly differentiated; in the pre-nostril fold, the cilia of a superficial neuromast, a mechanoreceptor, and an ampullary electroreceptor were also observed. Only 24 hours after hatching, the eyes became a conspicuous structure. At the time of the first feeding, the precocious development of the chemosensorial structures (olfactory pits and taste buds) may have reflected a higher larval capacity for perceiving and capturing the food particles in darkness. The observations of the inicial ontogeny of the neuromast and the cranial lateral line canals revealed that the development of the canals was apparent only one day after the beginning of the trunk lateral line neuromasts differentiation, which occurred at the second day of life. After this period, the cranial canals development proceeds until 16-17 days after hatching, at the metamorphosis stage, which could not be clearly defined. The head canals development initiated close to an individual neuromast and occurred at discrete stages. The distribution of trunk neuromasts along the horizontal septum was correlated with the configuration of the myomeres, where ...